The transition from prison to community initiative: an examination of gender responsiveness for female offender reentry - Holtfreter, Kristy (Criminal justice and behavior, 2014)
This review examines female offender reentry within the context of the Transition from Prison to Community Initiative (TPCI). Specifically, we consider each stage of the TPCI, noting the extent to which current reentry policies and practices can be informed by gender responsiveness. To illustrate further, we compare reentry approaches and correctional outcomes in two states. Directions for further research on female offender reentry and TPCI evaluations are discussed.